PROFIL PEKERJAAN DAN TENAGA KERJA INDUSTRI PERMESINAN MODERN TINGKAT ABSTRACT MENENGAH - Sugiyono, Sugiyono (LPMPP Universitas Negeri Yogyakarta, 2002)
This article is based on a research at first conducted toidentify thejob and job holder profiles in the intermediatelevelmodem machinery industry in order that the findingscould be used as materials for recommendations in developingvocational school management. However, after the researchwas conducted for one year, it turned out that not onlythose profiles but also a comparison between the developmentof vocational school (VC) graduates' competence at work andthatofsenior high school (SHS) graduates', a relation betweenindustry and school, and a competence-based evaluation systemon technicians' performance were esta-blished.The research was conducted by using a qualitative method.Atthe beginning IPTN was chosen as the industrialcomponentj,utunder study. Afterwards, the findings were validated with thoseidentified at eight other industrial components, namely, the in.dustrial companies PT Pindad, PT BharataBandung, PT BharataSurabaya, PT BBI Surahaya, PT PAL Surabaya, PT PindadMalang, PT Bharata Jakarta, and PT Tractor JakartaThe findings indicate that the job profiles in themodemmachinery industry using the CNC milling machine show sevenlevelsof difficulty. What is primarily demanded of themachine operator isan ability to give the machine instructionstodo a job. After receiving the same apprentice educationfor two years, thereis almost no difference in academicachievement and levelof failure on the job between the twogroupsofgraduates. However, in terms ofthe quantity ofreworkdone, theVC graduates are better than the SHS graduates.The rework done by theVC graduates has amounted to 27.8%while that done by theSHS graduates has amounted to 40.7%.Further, in termsof their awareness of the value of workand work ethos, theVC graduates are better than the SHSgraduates becausefor the former working at such a job has beentheir intention since their entrance into vocational school whilefor the latter working together with the VC graduates hasbeen only a resultof their inability to enter a university tocontinue their education after graduating from SHS. Afterworking togetherfor three years, the two groups' competenceat workis no longer colored by their educational background(VC or SHS) but by individual self-potential and managerialintervention. Thereis a relation between industrial and VScomponents, i.e., between the job profile and school curriculum,job holder profile and graduates' competence, industrialmachinery profileand VS practice equipment, and job holderevaluation system andVS practice evaluation. Industrial machinery operator achievement evaluation is based more on qualityand speedof work